Advertising slogans in brand recall: Utterance analysis versus self-reporting - Pestana, M. H.; Wan-Chen Wang; Moutinho, L. (Revista Portuguesa de Marketing, 2021)
The paper aims at contributing to a more effective creation and management of slogans, testing how slogans variety and emotions conveyed by slogans influences consumers’ willingness to recall a brand. A focus group setting was established to select appropriate brands and products for the study. Evidence was found that emotions, the antiquity of a brand and brand name have a positive relationship with brand recall, whereas a negative relationship is found with the length of slogans and the involvement presumed. Gender moderates the recall of brands and products, with men preferring brands having slogans with more extreme ratings of arousal, and women preferring slogans that are more spontaneous and sensitive.